Black Artists Shaping the World - Jackson, Sharna; Whitley, Zoé (London : Thames & Hudson, 2022)
Jackson, Sharna ; Achiampong, Larry ; Ra, El Anatsui ; Boyce, Sonia ; Campos-Pons, Maria Magdalena ; Cave, Nick ; Choumali, Joana ; Himid, Lubaina ; Ishag, Kamala Ibrahim ; Karuga, Rosemary ; Konaté, Abdoulaye ; Mahama, Ibrahim ; Marshall, Kerry James et al.
Written by award-winning Black British children’s author Sharna Jackson, Black Artists Shaping the World celebrates the diversity of work being produced today by Black artists from around the globe, introducing young readers to twenty-six contemporary artists from Africa and of the African diaspora. Sharna Jackson’s experience as a children’s author who has worked for over a decade in the cultural sector, both at Tate in London and at Site Gallery in Sheffield, is combined here with the curatorial expertise of Dr Zoé Whitley, Director of London’s Chisenhale Gallery and co-curator of the landmark Tate exhibition ‘Soul of a Nation: Art in the Age of Black Power’. Their book features artists working in a variety of media from painting, sculpture and drawing to ceramics, installation art and sound art. Artists featured include British Turner Prize-winning painters Lubaina Himid and Chris Ofili; renowned South African visual activist Zanele Muholi; Nigerian sound artist Emeka Ogboh; Sudanese painter Kamala Ibrahim Ishag; Kenyan-British ceramicist Magdalene Odundo; African-American artists Kerry James Marshall, Faith Ringgold, Amy Sherald and Kehinde Wiley; performance artist Harold Offeh; and moving image artist Larry Achiampong.(from publisher)
boek